Combined Effect of Organic Carbon and Arsenic on the Formation of Sediment-Hosted Gold Deposits: A Case Study of the Shahuindo Epithermal Deposit, Peru - (:unkn) unknown (Society of Economic Geologists, 2024)
Sediment-hosted gold deposits represent a significant portion of the world’s gold resources. They are characterized by the ubiquitous presence of organic carbon (Corg; or its metamorphosed product, graphite) and the systematic occurrence of invisible g...
Keywords: Depósitos de oro; Arsénico